Pengaruh Store Atmosphere, Kualitas Produk, Dan Kelengkapan Produk Terhadap Keputusan Pembelian Konsumen Pada Swalayan Koptan Dr. Iskak Tulungagung - Kartika Sari, Tyas; Widodo, Eko; Dian Evasari, Aprilia (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to see the influence of store atmosphere, product quality and product completeness on purchasing decisions at Dr. Iskak Tulungagung Koptan supermarket. The type of research uses associative quantitative research. The population in the study is Koptan supermarket consumers whose number is unknown, using the Cochran formula in determining the sample with a total of 385. The data processing application in this study uses SPSS software. The variables store atmosphere (X1), product quality (X2), and product completeness (X3) have a partial effect on purchasing decisions at the Koptan Dr. Iskak Tulungagung Supermarket. Store atmosphere has a regression coefficient of 0.104 (t count = 4.623 > t table 1.966, significance 0.000 < 0.05), product quality has a regression coefficient of 0.332 (t count = 9.926 > t table 1.966, significance 0.000 < 0.05), and product completeness has a regression coefficient of 0.334 (t count = 11.775 > t table 1.966, significance < 0.05). These three variables also have a simultaneous effect on purchasing decisions (F count = 59.789, significance 0.000 < 0.05). The product completeness variable has the most dominant influence with the regression equation Y = -1.874 + 0.104X1 + 0.332X2 + 0.334X3